Truth seekers voices of peace and nonviolence from Gandhi to Pope Francis - Cortright, David 1946- (Orbis Books, 2020)
"Readings on the theory and practice of nonviolence, from Gandhi, King, and other contemporary voices (including Pope Francis, Nelson Mandela, and many more)"--